PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP MOTIVASI BELAJAR SISWA SMA NEGERI 2 UJUNGBATU ROKAN HULU-RIAU - Wahyuni, Liza; -, Sohibun; Rita, Silvia (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2015)
This research was discuss about the influence of jigsaw cooperative learning model to student motivation. This research was conducted at SMAN 2 Ujungbatu in class X MIA 1. The purpose of this research to determine the effect of jigsaw learning model to student motivation. The instrument of this research is motivation questionship. Based on calculated using the data obtained by the correlation obtained that rvalue = 0.987 while rtable value = 0.316. Best on explanation above it can be concluded that rvalue is bigger that rtable (rhitung>rtabel), at the 5% significance level. It can be concluded that there are significant jigsaw cooperative learning model to motivate students of class X MIA 1 SMA Negeri 2 Ujungbatu